Educational Efficacy of the Use of Drama Method in Primary School Teaching - Branka Lepir-Šinik (Društvene i Humanističke Studije)
We are witnessing that today’s generations are growing up with an overwhelming presence of technology. This raises questions about how actively students read today, what kind of content they absorb, and whether they are able to communicate easily in both spoken and written forms. All of this requires active adaptation of teaching practices in order to maintain students’ attention and, above all, to convey the necessary knowledge and appropriate moral messages. One of the ways to engage students’ attention is the application of the dramatic method in classroom teaching. The dramatic method is a specific form of teaching based on role-playing, in which all students actively participate, while taking into account their individual differences. By imitating others or creating new characters, students are introduced to various problem situations that they solve together, thereby adopting educational and moral messages. This type of work develops students’ speaking, reading, and creative abilities, and also contributes to fostering a more positive attitude toward teamwork. The effectiveness of the dramatic method was verified through an ex-post-facto study with fifth-grade elementary school students. After three months of applying the experimental-research work, it was confirmed that there are statistically significant differences in favor of the dramatic method, as students in the experimental groups (E1 and E2) achieved statistically better results than those in the control groups (K1 and K2).